International validation of a behavioral scale in Parkinson's disease without dementia. Issue 5 (21st March 2015) - Rieu, Isabelle; Martinez‐Martin, Pablo; Pereira, Bruno; De Chazeron, Ingrid; Verhagen Metman, Leo; Jahanshahi, Marjan; Ardouin, Claire; Chéreau, Isabelle; Brefel‐Courbon, Christine; Ory‐Magne, Fabienne; Klinger, Helene; Peyrol, Fleur; et al.
Abstract The "Ardouin Scale of Behavior in Parkinson's Disease" is a new instrument specifically designed for assessing mood and behavior with a view to quantifying changes related to Parkinson's disease, to dopaminergic medication, and to non‐motor fluctuations. This study was aimed at analyzing the psychometric attributes of this scale in patients with Parkinson's disease without dementia. In addition to this scale, the following measures were applied: the Unified Parkinson's Disease Rating Scale, the Montgomery and Asberg Depression Rating Scale, the Lille Apathy Rating Scale, the Bech and Rafaelsen Mania Scale, the Positive and Negative Syndrome Scale, the MacElroy Criteria, the Patrick Carnes criteria, the Hospital Anxiety and Depression Scale, and the Mini‐International Neuropsychiatric Interview. Patients (n = 260) were recruited at 13 centers across four countries (France, Spain, United Kingdom, and United States). Cronbach's alpha coefficient for domains ranged from 0.69 to 0.78. Regarding test–retest reliability, the kappa coefficient for items was higher than 0.4. For inter‐rater reliability, the kappa values were 0.29 to 0.81. Furthermore, most of the items from the Ardouin Scale of Behavior in Parkinson's Disease correlated with the corresponding items of the other scales, depressed mood with the Montgomery and Asberg Depression Rating Scale (ρ = 0.82); anxiety with the Hospital Anxiety and Depression Scale—anxiety (ρ = 0.56); apathy with the Lille Apathy Rating Scale (ρ = 0.60). The Ardouin Scale of Behavior in Parkinson's disease is an acceptable, reproducible, valid, and precise assessment for evaluating changes in behavior in patients with Parkinson's disease without dementia. © 2015 International Parkinson and Movement Disorder Society